The relationship between the presence of EBV (Barr-Epstein virus) and the prevalence of breast cancer in Thi-Qar Governorate - عبود فارس ستار; فالح السعداوي نور; نعيم موسى حميد (University of Thi-Qar Journal of Science, 2016)
Breast cancer is a serious health problem and increasingly around the word, especially in developing countries is usually a killer disease cause an increase in the death rate.The study was designed to determine the relationship between Epstein-Barr virus (EBV) and the development of breast cancer in the province of Thi-Qar.Total specimens were (146) collected tissue sample and throw surgeries and breast biopsies for breast cancer patients ages ranging between(21-70) years, collected(52) sample of breast benign tumors same age groups to compare the ratio of the presence of virus(EBV) in both groups by immunohistochemistry(IHC).The result showed that the highest in fiction virus (EBV) were among malignant tumors group a rate of 42.00 cases.Compared with benign tumors that were all negative for this virus. The results showed that the highest percentage of the presence of EBV within the age groups (41-50) years and a rate of 5.00. The results al so showed that the tumorous grade (G2) at a rate of 22.00. The results of the tumors size are greater than 2 and less than 5 cm (T3) and at arte of 16.00.